Angels of the resistance - Salazar, Noelle (Mira, 2022)
"As bombs fall across Europe, fourteen-year-old Lien Vinke fears that the reality of war is inescapable. Though she lives a quiet life with her mother and older sister, Elif, in their small town of Haarlem, they are no strangers to heartache, having recently suffered an immeasurable loss. And when the Nazis invade the Netherlands, joining the Dutch resistance with Elif offers just the atonement Lien craves. Trained to shoot by their late father, the sisters are deadly wolves in sheep's clothing. They soon find themselves entrenched in the underground movement, forging friendships with the other young recruits, and Lien even discovers a kindred spirit in a boy named Charlie. But in wartime, emotional attachments are a liability she can't afford, especially when a deeply personal mission jeopardizes everything she holds dear--her friendships, her family, and her one shot at redemption" --